Pengembangan Media Flash Player dalam Pembelajaran Legenda untuk Siswa Kelas VIII SMP 2 Dawe Kudus - Nafi'ah, Azmatun; Kurniati, Endang (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2020)
Learning legend is learning that provides knowledge to students about an event that is considered really happened in ancient times. Legend stories contain good exemplary values ​​such as religious, social, and cultural values ​​that can serve as examples to better shape student personalities. Therefore, important legend learning is taught to students at school, but the learning of the legend at SMP 2 Dawe Kudus is of less interest to the students. The problem is because of the teaching and learning activities during this run in conventional and not varied and less use of LCD facilities that have been installed in each class. In addition, the learning of the legend in SMP 2 Dawe Kudus using the material Legend Bulusan from LKS in the form of text that is less contextual. Therefore, innovation is required to develop a more creative learning media such as flash media in the form of animated films in order to increase student interest in learning. The approach used in this research was Research and Development (R&D) which conducted with five stages, including potential and problem analysis, data collection, product design, design validation, and product testing. The subjects of this research were teachers of Javanese subject, students of grade VIII SMP 2 Dawe Kudus, interpreters of legend story, material expert, media expert, and media user. Data collection used in this research is questionnaires, interview guides, tests, and observation. The data was analyzed in qualitative-descriptive. The results showed students the experimental class that performed higher learning outcomes than the control class.